Linux nei he guan ce ji shu BPF = Linux observability with BPF / = Linux observability with BPF - Calavera, David; Fontana, Lorenzo (O'Reilly Media, Inc., 2020)
Detailed summary in vernacular field.
Keywords: Linux; Operating systems (Computers); Systèmes d'exploitation (Ordinateurs); operating systems